KEMAMPUAN GURU DALAM MERENCANAKAN PEMBELAJARAN HIGHER ORDER THINKING SKILLS (HOTS) DI SEKOLAH DASAR - Ari Surya Febriana; Eko Kuntarto; Alirmansyah Alirmansyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The ability to plan learning is a pedagogical ability that teachers must have. Learning Higher Order Thinking Skills (HOTS) should have been implemented by teachers in the RPP in order to support learnig activities that emphasize the development of critical thinking, creative and problem solving skills. This study aims to describe the ability of teachers in planning HOTS learning in the form of developing critical and creative thinking skills in solving problems in Sridadi 55/1 Primary School. This resarch was carried out at Sridadi 55/1 Public Elementary School, Muara Bulian District, Batanghari Regency, Jambi in even semester of the 2019/2020 school year. Data collection was obtained from RPP observations and supported by interviews with related parties to meet the data requirements regarding HOTS learning planning and documentation. Data analysis in this study used triangulation. The research method used is qualitative research with type of phenomenology that aimed to describe the phenomena experienced by the research subject in detail and in depth. The observations result showed that the Learning Implementation Plan (RPP) prepared by the teacher met the lerning planning indicators based on Higher Order Thinking Skills (HOTS). The result of the interview also strengthened the findings of the observation.Based on in-depth interviews conducted showed that the teacher had compiled the lesson plan and met the criteria of the HOTS-based lesson plan. The results showed that the class IIIA and VA teachers at Sridadi 55/1 Elementary School had designed a HOTS-based lesson plan with a fairly good category.